2019
DOI: 10.1175/jpo-d-19-0011.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Steadiness and Instability of the Intermediate Western Boundary Current between 24° and 18°S

Abstract: The Intermediate Western Boundary Current (IWBC) transports Antarctic Intermediate Water across the Vitória–Trindade Ridge (VTR), a seamount chain at ~20°S off Brazil. Recent studies suggest that the IWBC develops a strong cyclonic recirculation in Tubarão Bight, upstream of the VTR, with weak time dependency. We herein use new quasi-synoptic observations, data from the Argo array, and a regional numerical model to describe the structure and variability of the IWBC and to investigate its dynamics. Both shipboa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…We evaluate conversions within the kinetic energy budget by analyzing barotropic conversions as a mechanism for the DWBC anticyclones growth. We follow Vallis (2017) and Napolitano et al (2019) to calculate the horizontal shear production (HSP),…”
Section: The Growth Mechanism For the Dwbc Anticyclonesmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluate conversions within the kinetic energy budget by analyzing barotropic conversions as a mechanism for the DWBC anticyclones growth. We follow Vallis (2017) and Napolitano et al (2019) to calculate the horizontal shear production (HSP),…”
Section: The Growth Mechanism For the Dwbc Anticyclonesmentioning
confidence: 99%
“…In the DWBC, barotropic instabilities have been shown to play a role in regional dynamics (Biló et al, 2021) used an eddy-rich ocean model and revealed that barotropic instabilities dominate over baroclinic instabilities within the DWBC, with a gain in E KE resulting from strong horizontal shear. Moreover, the presence of the DWBC rubbing against the PP further advocates for the importance of horizontal shear instabilities, as they can draw energy from western boundary currents into eddies (e.g., Mata et al, 2006;Napolitano et al, 2019).…”
Section: The Eddy Corridor From the Pernambuco Plateau To 15°smentioning
confidence: 99%
See 1 more Smart Citation
“…Also, effects of topography, and eddy decay processes could be included. Recently, Napolitano et al (2019) showed that the variability in the region is dominated by westward-propagating eddies, which are likely to complicate the picture. To further address the mechanisms that drive the Vitória Eddy, we call for a hierarchy of models, from solutions as simple as ours to idealized primitive-equation simulations to complex regional numerical models.…”
Section: Linear Vs Nonlinear Dynamicsmentioning
confidence: 99%
“…Therefore, we are introducing the same bias in both the reconstructed and the "new" altimeter sea surface height. Moreover, we ensured that our reconstructed η fields (hereafter η rec ) using HYCOM's velocities preserved the variance of the original altimetric sea level anomaly field by multiplying each field by a constant factor defined as the RMS of the latter divided by the RMS η a (NAPOLITANO et al, 2019). Figures 3.16, 3.15 and 3.17 show η a , derived from altimeter's geostrophic velocities, and η rec , calculated using HYCOM's velocities and ISAS T and S, for all latitudes at each ocean basin.…”
Section: Sea Surface Height Reconstructionmentioning
confidence: 99%